A novel series of N-acyl substituted indole-linked benzimidazoles and naphthoimidazoles as potential anti inflammatory, anti biofilm and anti microbial agents. (January 2018) - Abraham, Rajan; Prakash, Periakaruppan; Mahendran, Karthikeyan; Ramanathan, Murugappan
Abstract: A novel N-acyl substituted indole-linked benzimidazoles and naphthoimidazoles were synthesized. Their chemical structures were confirmed using spectroscopic tools including 1 H NMR, 13 C NMR and CHN-elemental analyses. Anti inflammatory activity for all target compounds was evaluated in-vitro . The synthesized compounds hinder the biofilm formation and control the growth of the pathogen, Staphylococcus epidermis . Anti microbial activity of the compounds was evaluated against both Gram negative and Gram positive bacteria such as Staphylococcus aureus (MTCC 2940), Pseudomonas aeruginosa (MTCC424), Escherchia coli (MTCC 443) and Enterococcus fecalis . Graphical abstract: Image 1 Highlights: Synthesis of novel N-acyl substituted indole-linked benzimidazoles and naphthoimidazoles. Anti inflammatory activity for all target compounds was evaluated in-vitro. The synthesized compounds hinder the biofilm formation and control the growth of the pathogen, staphylococcus epidermis. Anti microbial activity of the compounds was evaluated against both Gram negative and Gram positive bacteria.